Elevational patterns of orchid diversity in mid-subtropical mountain forests of eastern China - Qinghua Zhan; Haihong Liao; Yuelong Liang; Zhong Zhang; Xingui Le; Yu Xiong; Lin Cheng; Wenqi Ding; Jian Lu; Yadong Zhou; Boyun Yang (Global Ecology and Conservation)
Orchidaceae serves as a “flagship” group in global biodiversity conservation efforts, drawing substantial interest from researchers in China, but research on the variation of orchid species diversity along elevational gradients in mid-subtropical mountain forests in China remains limited. In this study, we conducted an investigation of orchids across more than 1900 5 m × 5 m plots in six mountains located in central China, spanning an elevational range from 166 m to 1930 m, and then converted these survey data into the distribution data in 100 m elevational bands to study the trend of species richness (S), Shannon-Wiener index (H'), Simpson index (D), and Pielou evenness (e) of orchids variation along the elevational gradients. We discovered that although the diversity patterns vary among each mountain, overall, S, H', and D exhibit hump-shaped patterns, while e shows a slight monotonic increase pattern along the elevation. There are no significant difference between elevational patterns of diversity of terrestrial and epiphytic orchids. In addition, slope, canopy closure, and disturbance have no significant impact on all the four diversity indices, mean annual temperature positively correlates with species richness, while annual precipitation shows negative correlations with S, H', and D. Meanwhile, we also found that significant differences in the composition and abundance of orchid communities between high and low elevations. These results significantly enhance our understanding of elevation-dependent diversity patterns among rare and endangered plants in the mid-subtropical regions of China.